RECONSTRUCTION OF THE PROCEDURE FOR ENFORCING DECISIONS ON COLLATERAL IN SYNDICATED LOANS BASED ON THE PRINCIPLE OF EQUALITY BEFORE THE LAW - Sendi Sanjaya; Gunawan Widjaja; Hotma P. Sibuea; Dyah Ersita Yustanti (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The Indonesian constitution stipulates that Indonesia is a country based on the rule of law. In Indonesia, every citizen has equal standing before the law. This study analyses the problems of executing decisions on collateral in syndicated loans based on the principle of equality before the law. The legal issues examined in this dissertation are as follows. First, how is the legal construction of executing decisions on collateral in syndicated loans? Second, what are the legal consequences of the execution of judgments against collateral in syndicated loans for other creditors in the syndicate structure? Third, what is the appropriate legal reconstruction to overcome the obstacles to the execution of judgments against collateral in syndicated loans based on the principle of equality before the law? The research method used in this dissertation is a legal-normative research method. The results of the research are as follows. First, the execution of a judgment against collateral in syndicated loans is not in accordance with the provisions of civil procedural law as regulated by HIR/RBg. Second, in the context of the execution of a judgment against collateral in syndicated loans, there is a legal vacuum (law). Third, the legal vacuum in the regulation of the execution of judgments against collateral in syndicated loans results in the execution not complying with the principle of equality before the law, thereby causing losses to certain parties, especially in terms of the distribution of the proceeds of the execution. In relation to the three conclusions above, the author can offer the following suggestions. First, in every credit agreement deed, the facility agent and guarantor agent must be regulated in the credit agreement deed as a single entity. Second, the HIR/RBg civil procedure law needs to be amended and a national civil procedure law needs to be established in accordance with societal developments. Third, the new civil procedure law must be guided by the principle of equality before the law.